Menelisik Relevansi Pancasila Sebagai Spiritualitas Hidup Bangsa Indonesia Yang Majemuk - Bartolomeus Samho; Rudi Setiawan (Lembaga Penelitian dan Pengabdian Universitas Negeri Manado, 2022)
Pancasila is the spirituality that animates the life of the Indonesian nation. This paper aims to describe Pancasila as the spirituality of life for the Indonesian people. Based on the results of research in 2015 entitled